2020
DOI: 10.1002/jccs.202000055
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the morphology of polyvinylidene fluoride membrane by incorporatingMOF‐199 nanomaterials for improving water permeation with antifouling and antibacterial property

Abstract: MOF-199@PVDF composite membranes are prepared by blending with different amounts of ultrasonic synthesized MOF-199 nanomaterials for improving the pure water flux (PWF) and achieving better antifouling and antibacterial performance. The membrane morphology, elemental composition, and surface properties are analyzed by various means of characterizations, including scanning electron microscopy, energy-dispersive X-ray spectroscopy, and water contact angle measurements. The performance of the modified membranes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…57 Also, it can be seen that the Cu 2+ metal ions are absorbed by bacteria and damage the cytomembrane, hence causing the death of the microorganisms. 58,59 These results show that the PVDF/MOF-199 membrane has greater and more efficient antibacterial characteristics, which creates greater routes for the future to eradicate biofouling problems in the membrane process in future water treatment processes.…”
Section: Resultsmentioning
confidence: 93%
“…57 Also, it can be seen that the Cu 2+ metal ions are absorbed by bacteria and damage the cytomembrane, hence causing the death of the microorganisms. 58,59 These results show that the PVDF/MOF-199 membrane has greater and more efficient antibacterial characteristics, which creates greater routes for the future to eradicate biofouling problems in the membrane process in future water treatment processes.…”
Section: Resultsmentioning
confidence: 93%
“… Support MOF Sonication properties: Time/Frequency/power Filtration process Permeability-permeation Rejection/selectivity Ref. Matrimid ZIF-9 Direct sonication: 0–10 min/20 kHz/ 200 W Indirect sonication:0–10 min /40 kHz/ 120 W CO 2 /CH 4 Separation 300 barrer Selectivity: 85 % [142] Commercial NF TFC membranes Cu-MOF 30 min/ 20 kHz/ 100 W Dye removal 10 LMH Rejection: Methyl blue:90 % Methyl orange: ∼95 % for [143] PVDF CU-BTC 60 min/ 40 kHz/ 60 W BSA separation (antifouling test) 185.05 LMH @ 1 bar Rejection: bovine serum albumin (BSA): 94 % [144] PES Ag-MOF 60 min/ 24 kHz/ 80 W FO process @ 2 M NaCl (draw solution): 81 LMH Js/Jw = 0.13 [145] PES Ce-MOF 30 min/ 30 kHz/ 60 W Dye removal 21.2 LMH Rejection: Direct Red 16: 99 % [99] PS Cu-BTC 30 min/ nm*/ nm landfill leachate treatment 190 LMH @ 3 bar Rejection: landfill leachate (COD: 18000 mg/L): 47 % [102] PES TMU-5 30 min/ nm/ 350 W powder milk solution (antifouling test) 123.212 @ 3 bar Rejection: powder milk > 98 % [97] * Not mentioned. …”
Section: Ultrasonically Synthesized Mofs For Membrane Applicationsmentioning
confidence: 99%
“…The characterizations revealed that the presence of Cu-MOF nanocrystals in the selective layer could significantly enhance the membrane hydrophilicity, fouling resistivity (∼90 % improvement in flux recovery ratio), and dye rejection (from ∼ 26 % to 90 % for methyl blue, and ∼ 28 % to ∼ 95 % for methyl orange). Sonication was also utilized to produce MOF-PVDF composite membranes using MOF-199 (CU-BTC) for microfiltration tests (TMP: 0.1 MPa) [144] . The incorporation of MOF increased the water flux from 12.75 LMH for the pristine membrane to 185.05 LMH and the bovine serum albumin (BSA) rejection was maintained at a high level ( 94 %).…”
Section: Ultrasonically Synthesized Mofs For Membrane Applicationsmentioning
confidence: 99%
“…In addition, biofouling is also an important issue that restricts the development of separation technology. [19] Newly developed MOF materials make up for the shortcomings in the above-mentioned research fields. Many superior advantages, such as high surface area, considerable porosity, and adjustable pore structure, make MOFs characterized with excellent adsorption, catalysis, and membrane separation capabilities.…”
Section: Application Of Mofs In Sewage Treatmentmentioning
confidence: 99%
“…Among them, heavy metal enormous concern because of their distinctive properties in catalytic degradation, [14] separation, [15] adsorption, [16] electrochemical sensors, [17] catalytic water splitting to hydrogen, [18] and antibacterial engineering. [19] Using MOF as precursor, composite materials can be prepared by changing metals, replacing organic ligands or functionalizing for the target of improving the performance of MOF. Composites are designed and synthesized according to realistic needs to obtain special functions and structures, which usually integrate the advantages of each component.…”
Section: Introductionmentioning
confidence: 99%